COMPARATIVE ANALYSIS OF THE ECONOMIC PROFITABILITY OF THE EXPORT OF FRESH PINEAPPLE AND ITS JUICE PRODUCED IN BENIN REPUBLIC - BIAOU, CHABI FÉLIX; YAI, D. Emmanuel; BIAOU, GAUTHIER; ACCLASSATO HOUENSOU, DENIS (My University, 2023)
In recent years, the rapid increase in pineapple production and its juice has been accompanied by an increase in its exports to various sub-regions. To assess the profitability of these exchanges, surveys were conducted among producers, processors and exporters of this commodity. In this study, the methodological approach includes the use and analysis through the Cost-Financial and Economic Benefit ratios nominal and effective protection coefficients and the ratio of comparative advantage. The results show that the export of fresh pineapple to hinterland countries is on the one hand, more profitable than that of pineapple juice because of the proliferation of sugar-sweetened beverages in the sub-region. On the other hand, it is more profitable than its export to Europe.
Keywords: Fresh pineapple; financial and economic; cost-benefit ratios; domestic resource costs; tradable and non-tradable factors.